2021
DOI: 10.1007/s11896-021-09438-x
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Male Role Norms, Social Support, and Symptoms of Post-traumatic Stress Disorder Among Male Polish Police Officers

Abstract: Police officers’ work involves the exposition to traumatogenic stimuli. The aim of the research is to investigate potential associations between post-traumatic stress disorder and the traditional masculinity norms and social support. Three questionnaires were used: the Impact of Event Scale-Revised adapted by Juczyński and Ogińska-Bulik (2009), the Social Relations Scale (Skarżyńska 2002), and the Male Role Norms Scale translated by the authors of this paper. The sample comprised 111 male active service member… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 109 publications
(123 reference statements)
0
4
0
Order By: Relevance
“…In this thematic review, five studies (25%) of those included highlight the importance of organizational culture [ 42 , 47 , 48 , 49 , 50 ]. Again, the studies show both positive and negative effects of a particular organizational culture.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this thematic review, five studies (25%) of those included highlight the importance of organizational culture [ 42 , 47 , 48 , 49 , 50 ]. Again, the studies show both positive and negative effects of a particular organizational culture.…”
Section: Resultsmentioning
confidence: 99%
“…In an interesting study by Gutschmidt and Vera [ 47 ], their results indicated that the type of organizational culture (e.g., hardworking cultures, team cultures) predicted both the maladaptive strategies used by police officers and their job satisfaction. In a study by Sitko-Dominik and Jakubowski [ 48 ], results showed a relationship between adherence to traditional masculinity norms (e.g., anti-femininity) and PTSD symptomatology (related to fear of losing emotional control). More specifically, their findings indicated that in male police officers, coping with stress could be negatively affected by their adherence to certain social role norms (e.g., hypermasculinity) acquired during the socialization process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Masculine gender role discrepancy is conceptually defined as the perceptual characterization of men who deviate from the established societal norms associated with traditional masculinity [ [1] , [2] , [3] ]. As hegemonic masculinity is the standard for most men [ 4 , 5 ] and male roles are strongly affected by stereotypes [ 6 , 7 ], to appear “manly” men are pressured to exhibit a comprehensive range of characteristics associated with masculinity, and this perpetual confirmation becomes an ongoing process, reinforcing societal norms and fortifying the notion of what it means to be a man [ 8 , 9 ]. Moreover, boys acquire a learned expectation that the contravention of established masculine norms will engender unfavorable social ramifications [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%